The Green Library Concept: Exploring Microlibrary Warak Kayu Semarang - Nur Fatwa, Annisa; Ega Winastwan, Rheza (Perpustakaan Universitas Gadjah Mada, 2025)
Microlibrary Warak Kayu, located in Semarang City, Central Java Province, is a community-based library distinguished by its innovative architectural design and the use of environmentally friendly materials as a concrete manifestation of its commitment to sustainable development. This study aims to provide an in-depth analysis of the implementation of the green library concept at Microlibrary Warak Kayu as a model for local-level sustainable library practices. A descriptive qualitative approach was employed, with data collected through field observations, in-depth interviews, and documentation studies to obtain a comprehensive understanding of the sustainability initiatives implemented. The findings indicate that green library principles have been applied holistically, including the utilization of energy-efficient buildings and facilities, the use of certified timber materials, the integration of green office practices in operational management, and the strengthening of sustainable economic initiatives through collaboration with local communities. Additionally, the library provides services that promote environmental literacy, fosters inclusive social interactions, and implements systematic environmental management strategies aligned with the Sustainable Development Goals. These findings demonstrate that Microlibrary Warak Kayu functions not only as a center for literacy, but also as a public space that educates and exemplifies sustainable practices, making it a relevant reference for the development of green libraries in Indonesia. Keywords: green library; Microlibrary Warak Kayu; sustainable library